2015
DOI: 10.1200/jco.2015.33.7_suppl.140
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy (ADT) plus docetaxel (D) versus ADT alone for hormone-naïve metastatic prostate cancer (PCa): Long-term analysis of the GETUG-AFU 15 phase III trial.

Abstract: 140 Background: ADT is standard treatment for metastatic PCa. Recently, the E3805 trial reported a survival benefit for (ADT+D) in high volume disease (HVD) patients, whereas the GETUG-15 trial did not demonstrate a survival improvement among a less selected group of patients (pts) with hormone-naïve metastatic PCa. We report an updated analysis of overall survival (OS) of the GETUG 15 trial and aligned the definition of HVD and low volume disease (LVD) subgroups. Methods: Long-termOS was analyzed in the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 0 publications
1
40
0
5
Order By: Relevance
“…For OS, the subgroup analysis of patients according to disease volume (high vs low volume) was available for two trials [23,27]. In both trials, high-volume disease was defined as the presence of at least four bone lesions and at least one lesion in any bone beyond the spine/pelvis or the presence of visceral metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…For OS, the subgroup analysis of patients according to disease volume (high vs low volume) was available for two trials [23,27]. In both trials, high-volume disease was defined as the presence of at least four bone lesions and at least one lesion in any bone beyond the spine/pelvis or the presence of visceral metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…Медиана ОВ составила 46,5 мес в группе АДТ и 60,9 мес в группе АДТ + доцетаксел (ОР 0,9; 95 % ДИ 0,7-1,2). Результаты исследования GETUG 15 были схожими с теми, что и в проведенном позднее иссле-довании CHAARTED, однако исследование GETUG 15 показало незначительное улучшение ОВ в группе АДТ + доцетаксел, которое составило около 4 мес [39].…”
Section: Introductionunclassified
“…Results from three phase III clinical studies that evaluated the role of docetaxel in mHSPC, have been recently reported: CHAARTED study (E3805) [Sweeney et al 2015], GETUG-AFU 15 [Gravis et al 2013;Gravis et al 2015] and the STAMPEDE study [James et al 2016a;James et al 2016b].…”
Section: Metastatic Hormone-sensitive Prostate Cancermentioning
confidence: 99%
“…The potential use of docetaxel in the context of hormone-sensitive disease has also been explored in the GETUG-AFU 15 study [Gravis et al 2013;Gravis et al 2015]. GETUG-AFU 15 was a randomized, open-label, phase III study in patients with newly diagnosed mHSCP.…”
Section: Getug-afu 15 Studymentioning
confidence: 99%